Significant genetic differentiation between native and introduced farmed Burmese pythons and low risk of genetic introgression from escaped farmed individuals in Hainan Island - Jiao Qing; Xiaofei Zhai; Shaopeng Yu; Feiyun Tu; Tongliang Wang; Jichao Wang (Conservation Science and Practice)
Abstract The Burmese python (Python bivittatus) is one of the most endangered pythons and is commonly traded in the international pet industry. In addition to wild P. bivittatus, domesticated individuals from farms have been living on Hainan Island for nearly 20 years. The intentional release or accidental escape of farmed P. bivittatus may lead to risks, such as genetic introgression or competition for space and food, owing to the genetic differences between the two populations and limited resources. Our objective was to better understand the genetic background of P. bivittatus and genetic introgression between native and introduced farmed populations. We conducted mitochondrial DNA (mtDNA) sequencing (138 specimens) and whole‐genome resequencing (110 specimens) of P. bivittatus from farm and wild populations on Hainan Island. Genetic analysis suggested two highly differentiated clusters (VN and HN clades), Fst = 0.22. The HN clade included samples that originated from southern China and Hainan and represented native individuals of Hainan Island, whereas the VN clade most likely originated from Vietnam, as expected based on the Vietnamese origin of the farm. The results of ADMIXTURE analysis indicated three possible genetic components, one of which can be viewed as the VN clade, and the remaining two genetic components both belong to the HN clade. We identified a small number of shared haplotypes between the farmed and wild populations, indicating that both farmed and wild samples included individuals from VN and HN clades. In addition, only one F1 generation hybrid individual between the two clades was found, suggestive of low gene flow. Thus, the probability of genetic introgression between HN and VN clades is low and poses a low threat to the genetic integrity of the native P. bivittatus on Hainan Island; however, we cannot underestimate the risk of escaped individuals, which should be closely monitored.